2018
DOI: 10.1039/c8cc07440b
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent materials of lanthanoid complexes hosted in zeolites

Abstract: Our emphasis is on understanding the influence of microenvironments of the void spaces on the luminescence performances of the encapsulated lanthanide complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 67 publications
0
23
0
1
Order By: Relevance
“…A novel Eu IIIsilica hybrid nanoparticle was developed by using a doubly binding TPPOÀ Si(OEt) 3 (TPPO: triphenyl phosphine oxide) linker. The TPPOÀ Si(OEt) 3 was confirmed by 1 H, 31 P, 29 Si NMR spectroscopy and single-crystal X-ray analysis. Luminescent Eu(hfa) 3 and Eu(tfc) 3 moieties (hfa: hexafluoroacetylacetonate, tfc: 3-(trifluoromethylhydroxymethylene)camphorate) were fixed onto TPPOÀ Si(OEt) 3 -modified silica nanoparticles, producing Eu(hfa) 3 (TPPOÀ Si) 2 -SiO 2 and Eu(tfc) 3 (TPPOÀ Si) 2 -SiO 2 , respectively.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…A novel Eu IIIsilica hybrid nanoparticle was developed by using a doubly binding TPPOÀ Si(OEt) 3 (TPPO: triphenyl phosphine oxide) linker. The TPPOÀ Si(OEt) 3 was confirmed by 1 H, 31 P, 29 Si NMR spectroscopy and single-crystal X-ray analysis. Luminescent Eu(hfa) 3 and Eu(tfc) 3 moieties (hfa: hexafluoroacetylacetonate, tfc: 3-(trifluoromethylhydroxymethylene)camphorate) were fixed onto TPPOÀ Si(OEt) 3 -modified silica nanoparticles, producing Eu(hfa) 3 (TPPOÀ Si) 2 -SiO 2 and Eu(tfc) 3 (TPPOÀ Si) 2 -SiO 2 , respectively.…”
mentioning
confidence: 88%
“…As reported in our previous work, HFA has a low vibrational frequency for decreasing the nonradiative rate constant, [39] and TPPO can form of antisymmetric structure for increasing of the radiative rate constant. [40,41] Therefore, in this study, we synthesized a new triphenylphosphine oxide compound TPPOÀ Si(OEt) 3 and identified it by 1 H, 31 P, 29 Si NMR spectroscopies and singlecrystal X-ray analysis. Using Eu(hfa) 3 complex with TPPOÀ Si-(OEt) 3 ligand covalently bonded to the silica nanoparticle through two binding sites, we developed a nanoluminophore Eu(hfa) 3 (TPPOÀ Si) 2 -SiO 2 (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…Внаслідок сорбції досліджуваного компонента на твердих носіях утворюються жорсткі структури, які сприяють зменшенню міжмолекулярного ____________________  Сташків О., Василечко В., Гамерник Р. та ін., 2021  переносу енергії, крім того, наявний ефект концентрування [4]. Сорбційнолюмінесцентний метод часто використовують для визначення неорганічних [4][5][6][7][8] та органічних [9][10][11] речовин. Цей метод дає можливість поєднувати сорбційне концентрування речовин з наступним люмінесцентним визначенням безпосередньо в сорбенті, не проводячи десорбції.…”
Section: вступunclassified
“…Luminescent complexes of trivalent lanthanide ions are of widespread interest for advanced technologies [1][2][3][4][5]. Selected examples of application include electronic devices [6,7], electroluminescent materials [8,9], photovoltaics [10], biological probes and multifunctional materials [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%